Developing Puzzles Laboratory Safety Symbols for Laboratory Introduction - Zamhari, Muhammad; Setiawati, Estriana Murni (Proceeding International Conference on Science and Engineering, 2017)
This work describes a study of puzzles development of laboratory safety symbols for laboratory introduction. The puzzles were purposed as a learning media for students prior to work in chemistry and science laboratory. The puzzles consisted of two different standard systems, Material Safety Data Sheet (MSDS) and National Fire Protection Association (NFPA) 704. For instructional development, the media was developed using four-D model (Define, Design, Develop, and Disseminate). This work was in develop stage and the media was qualitatively tested in State Islamic University Sunan Kalijaga, Yogyakarta, Indonesia and non-university student visited to laboratory in Faculty of Science, Prince of Songkla University, Thailand by quiz-team method.